2005
DOI: 10.1159/000086208
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene-Related Peptide during Sweating in Young Healthy Women

Abstract: Calcitonin gene-related peptide (CGRP) concentrations are increased in postmenopausal women and castrated men with symptomatic flushing. We wanted to determine if a CGRP increase exists in the plasma of healthy fertile-age women during sweating. Plasma concentrations of CGRP were measured by radioimmunoassay at maximal sweating during a sauna session and during bicycle exercise both at maximal and 70% of maximal work capacity in 8 healthy women of fertile age. Plasma concentrations of CGRP were unaffected (>90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…QSART volume is dependent on the number of sudomotor fibers responding to iontophoretic simulation, the number of efferent fibers activated in the reflex arc, and the amount of sweat produced by individual glands in response to stimulation (Schlereth et al, 2005). Variability in sweat gland output may be because of humoral factors (Spetz et al, 2005) or differences in local skin temperature (Ogawa and Sugenoya, 1993) and could contribute to the lability of the sudomotor response. Variability in sweat gland output may be because of humoral factors (Spetz et al, 2005) or differences in local skin temperature (Ogawa and Sugenoya, 1993) and could contribute to the lability of the sudomotor response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QSART volume is dependent on the number of sudomotor fibers responding to iontophoretic simulation, the number of efferent fibers activated in the reflex arc, and the amount of sweat produced by individual glands in response to stimulation (Schlereth et al, 2005). Variability in sweat gland output may be because of humoral factors (Spetz et al, 2005) or differences in local skin temperature (Ogawa and Sugenoya, 1993) and could contribute to the lability of the sudomotor response. Variability in sweat gland output may be because of humoral factors (Spetz et al, 2005) or differences in local skin temperature (Ogawa and Sugenoya, 1993) and could contribute to the lability of the sudomotor response.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that electrode position was nearly identical between successive tests (i.e., the same population of sudomotor fibers was activated), individual sweat gland output may have influenced sweat volumes between tests (Schlereth et al, 2005). For example, Spetz et al (2005) reported hormonal variations in sweat responses in women. For example, Spetz et al (2005) reported hormonal variations in sweat responses in women.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium may play a particularly important role. Pronounced alterations in plasma calcitonin gene-related peptide, a potent and partly endothelium-dependent vasodilator, are observed among women with hot flashes15 and acutely during hot flashes15 but not during other sweating 16. However, the role of the vasculature in hot flashes has received limited attention.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoestrogenic states are associated with impaired endothelial functioning,12, 13 and estrogen use among younger postmenopausal women has been associated with fewer calcified plaques in the coronary arteries 14. Further, potent vasodilators such as calcitonin gene-related peptide are released during hot flashes but not during exercise or sweating 15, 16. Finally, risk factors for hot flashes are also cardiovascular risk factors, including obesity and smoking 1…”
mentioning
confidence: 99%
“…In resting humans, the blood concentration of αCGRP shows a large inter-individual variability (14.0–132.5 pg·mL −1 ) [ 19 ], but it seems to be very constant intra-individually [ 20 ]. Although baseline blood αCGRP seems to be unaffected by training [ 21 ], several independent works found that this neuropeptide transiently increases in the blood in response to exercise [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, fifteen years after the description of this phenomenon [ 21 ], the physiological significance of αCGRP release during exercise is still unknown.…”
Section: Introductionmentioning
confidence: 99%